Vertical-horizontal actor collaboration in governance network: a systematic review - Hendra, Oke; Prasojo, Eko; Fathurrahman, Reza; Pilbeam, Colin (Springer, 2024)
This research proposes a categorization framework to analyse multi-actor collaboration variations in governance network. It examines both vertical (government levels) and horizontal (sectors) interactions. This study reviewed 92 academic articles, adhering to the PRISMA methodology and utilizes 2 × 2 and "who-how-what" frameworks to capture the breadth of vertical-horizontal collaboration arrangements. The study identifies a rise in multi-actor collaborations and a dominance of qualitative research. It exposes research gaps: limited cross-sectoral and international actor studies, and under-researched sectors beyond environment. The proposed framework, capturing actors, levers, purposes, and context, aims to guide future research on vertical-horizontal actor collaboration in governance network.
Keywords: Governance network; PRISMA methodology; Systematic review; Vertical-horizontal actor collaboration; 4407 Policy and Administration; 44 Human Society; Political Science & Public Administration; 3505 Human resources and industrial relations; 3507 Strategy, management and organisational behaviour